Gaps between technical-productive education and sustainability principles: a challenge for the current work context - Sifuentes Herrera, Eufrosina (2024)
Objective: This study aims to analyze the gaps between technical-productive education and the principles of sustainability in the Huanuco region (Peru), as well as to propose strategies to close this gap and promote the formation of relevant and responsible skills in the current work context. Materials and methods: A qualitative approach was used, including semi-structured interviews and focus groups with teachers, students, and administrators of technical-productive educational institutions in the Huánuco region. A thematic analysis of the data collected it is was carried out to identify perceptions, challenges, and proposals related to the integration of sustainability in technical-productive education. Results: The results show a limited understanding of sustainability among teachers and students, as well as institutional and structural challenges to the integration of these principles into educational programs. Gaps in the perception and relevance of technical skills taught in relation to sustainability were identified. Measures were proposed such as teacher training, the review of curriculums, the development of educational materials, and collaboration with industry to address these shortcomings. Conclusions: Closing the gaps between technical-productive education and sustainability is essential with the objective of prepare to the students for a sustainable and responsible labor market. Is requires a commitment to Institutional and collaboration among all the parties interested to implement effective strategies. This study highlights the importance of transforming technical education into a driver of sustainable development, both in the Huánuco region and in other contexts.